Metabolic and technical changes in swimmers during a 100-m all-out front crawl - Almeida-Coelho, J.; Fernandes, R. J.; Vilas-Boas, J. P. (Trends in Sport Sciences, 2016)
Introduction: Swimming performance depends on the swimmer`s capacity to generate mechanical power and resist fatigue. As short intense exercise (up to 1 min in duration) depends heavily on anaerobic energy release, glycolytic contribution seems fundamental for performing the 50 m and 100 m swimming events. Swimming velocity is also highly dependent on swimmers` technique, which could be assessed with stroke frequency (SR) and stroke length (SL). Aim of Study: The study aimed to analyse changes of metabolic and technical parameters in swimmers performing a maximal 100-m all-out front crawl. Material and Methods: Seven well-trained male swimmers (51.79 + 1.1 s at 100 m freestyle), performed an 100-m all-out front crawl, with intermediate velocity, SR, and SL assessed at each 25 m of the covered test distance. To estimate changes in blood lactate concentrations ([La-]), the blood lactate increasing speed (BLIS) methodology was used, with swimmers performing 25, 50 and 75 m front crawl bouts (controlled with a visual pacer) at the previously assessed velocities in each split of the 100 m test. [La-] were assessed before and immediately after each trial (until reaching the peak [La-]), with BLIS determined with the time rate of net [La-] per split. SR and SL were assessed using a video camera and a chronometer. Means and SD, Spearman`s rank correlation coefficient and ANOVA for repeated measures were used (p < 0.05) for statistical analysis. Results: The average velocity of the 100 m test was 1.89 ± 0.15 m·s-1, decreasing during the first three laps (and increasing in the last 25 m), concurrently with an increase in SR and a decrease in SL. [La-] increased throughout the test (to 15.01 ± 1.42 mmol·l-1), and BLIS diminished during the first three laps, while increasing during the last one. Conclusions: Glycolytic power determines the first 25 m lap of a maximal 100 m front crawl effort, causing fatigue effects measured with simple biomechanical parameters. A volitive effect of metabolic pathways can be observed in the last 25 m.